Earnings Management and Firm Value: Moderating Role of Independent Commissioner in Indonesia - Amrie Firmansyah; Dinar Limarwati; Yola Sri Ratna Alfiyani (Politeknik Keuangan Negara STAN, 2023)
Research objective: this study examines the empirical effect of earnings management on firm value and the moderating role of independent commissioner in relationship between earnings management and firm value. Method: this study employs data derived from financial statements of technology sector companies listed on the Indonesia Stock Exchange in the 2020 and 2021 periods. The data is sourced from www.idx.co.id. This study uses quantitative research methods. Based on purposive sampling, the number of samples used in this study is 34 observations. Research finding: the study results suggest that earnings management is negatively associated with firm value, while independent commissioner does not have a moderating role in the relationship between earnings management and firm value. Practical implication: this research is expected to contribute to investment policymaking in the technology sector in Indonesia.